The Development of Learning Activities for Online Visual Elemental Skills in Visual Arts According to Davies's Concept for Mathayomsuksa 4 Students - Mahad, Anon; Pantasri, Pittayawat (Interdisciplinary Academic and Research Journal, 2023)
Visual elements are an aesthetic medium that students must learn to understand the elements of visual elements in visual arts to combine them into shapes that can convey meaning along the subject line or concept that is the destination. However, due to the nature of visual arts subjects are practical subjects. Knowledge, memory, and understanding of the theory are also part of the practice that has accumulated in the knowledge and understanding that can be measured by the achievement test. The purposes of this research were to: (1) Development of Learning Activities for Online Visual Elemental Skills in Visual Arts According to Davies's Concept with an efficiency criterion of 80/80. (2) Compare learning achievement on visual elements in visual arts topics before and after using Davies’ Concept. (3) study of practical skills in visual elements. And (4) study for the satisfaction of students who learned through Davies’ Concept. The samples were 39 students of Mathayomsuksa 4/4 in the 1st semester of the academic year 2021 at Sarakham Phitthayakom School, Secondary Education Service Area Office Mahasarakham, and the samples were selected via the Cluster Random Sampling. The instruments used in this research consisted of the learning plan, achievement test, practice skills assessment, and the questionnaire of student satisfaction. The statistics used in data analysis were percentage, mean, standard deviation, and t-test (Dependent Samples). The findings of this research revealed that: (1) the Learning Activities for Online Visual Elemental Skills in Visual Arts According to Davies's Concept found that the efficiency was 81.06/80.15, which showed the efficiency with the 80/80 criterion. (2) The average post-test score of the student after using Davies's Concept was higher than the pretest at the .05 level of statistical significance. (3) students had practical skills in visual elements after using Davies's Concept at a high level (77.69%). And (4) Students had satisfaction with Learning Activities for Online Visual Elemental Skills in Visual Arts According to Davies's Concept at a high level.